New methods to engineer and seamlessly reconfigure time triggered Ethernet based systems during runtime based on the PROFINET IRT example - Wisniewski, Lukasz (Technologien für die intelligente Automation, Technologies for Intelligent Automation, 2017)
The objective of this dissertation is to design a concept that would allow to increase the flexibility of currently available Time Triggered Ethernet based (TTEB) systems, however, without affecting their performance and robustness. The main challenges are related to scheduling of time triggered communication that may take significant amount of time and has to be performed on a powerful platform. Additionally, the reliability has to be considered and kept on the required high level. Finally, the reconfiguration has to be optimally done without affecting the currently running system.